2001
DOI: 10.1046/j.1365-2672.2001.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen on the survival of non-Saccharomyces yeasts during mixed culture fermentations of grape juice with Saccharomyces cerevisiae

Abstract: Our study reveals new knowledge on the mechanisms underlying the succession of yeasts during wine fermentations. This knowledge may be of importance when creating defined, mixed starter cultures for the controlled production of wines with a wide range of flavour compositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 11 publications
11
104
2
5
Order By: Relevance
“…Granchi et al (1998) reported that numbers of K. apiculata declined once S. cerevisiae became dominant rather than when the fermentation temperature and ethanol concentration reached values known to inhibit apiculate yeast growth. It has also been reported that T. delbrueckii and K. thermotolerans are less tolerant to low oxygen levels and it is this, rather than ethanol toxicity, that affects their growth and leads to their death during fermentation (Hansen et al, 2001). It was also shown that a cell-cell contact mechanism in the presence of high concentrations of viable S. cerevisiae yeasts played a role in the inhibition of these two non-Saccharomyces species (Nissen et al, 2003).…”
Section: The Role and Use Of Non-saccharomyces Yeasts In Wine Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granchi et al (1998) reported that numbers of K. apiculata declined once S. cerevisiae became dominant rather than when the fermentation temperature and ethanol concentration reached values known to inhibit apiculate yeast growth. It has also been reported that T. delbrueckii and K. thermotolerans are less tolerant to low oxygen levels and it is this, rather than ethanol toxicity, that affects their growth and leads to their death during fermentation (Hansen et al, 2001). It was also shown that a cell-cell contact mechanism in the presence of high concentrations of viable S. cerevisiae yeasts played a role in the inhibition of these two non-Saccharomyces species (Nissen et al, 2003).…”
Section: The Role and Use Of Non-saccharomyces Yeasts In Wine Productionmentioning
confidence: 99%
“…Non-Saccharomyces yeasts have poor tolerance to low oxygen availability, especially compared with S. cerevisiae (Hansen et al, 2001). The removal of oxygen by vigorously fermenting S. cerevisiae can contribute to an early death of some nonSaccharomyces yeasts.…”
Section: Factors Affecting Growth Of Non-saccharo-myces Yeasts Duringmentioning
confidence: 99%
“…Previous studies demonstrated that S. cerevisiae outcompetes non-Saccharomyces yeasts during real and simulated wine fermentation conditions (Holm Hansen et al, 2001;Mendoza et al, 2007;Moreira et al, 2005Moreira et al, , 2008. Diverse factors, such as the ethanol produced during fermentation, killer toxins, nitrogen limitation or a better adaptation to the environmental conditions (including temperature), could influence ecology and competition between yeast species (Casey and Ingledew, 1986;Heard and Fleet, 1987;Monteiro and Bisson, 1991;Querol and Fleet, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Documented evidence suggest that in the early stages of fermentation, fruit surfaces are dominated by non-Saccharomyces yeasts, bacteria, and filamentous fungi [73,74] but Saccharomyces yeasts dominate the microbial population at the end of fermentation in anaerobic conditions. This suggests that Saccharomyces yeasts are the most dominant alcoholic fermentation microorganisms [75][76][77]. Even in the presence of oxygen, S. cerevisiae, is the predominant yeast species responsible for the production of ethanol [78,79].…”
Section: Yeastsmentioning
confidence: 99%